The thermal boundary resistance at semiconductor interfaces: a critical appraisal of the Onsager vs. Kapitza formalisms. Issue 35 (22nd August 2018) - Rurali, Riccardo; Cartoixà, Xavier; Bedeaux, Dick; Kjelstrup, Signe; Colombo, Luciano
Abstract : We critically readdress the definition of thermal boundary resistance at an interface between two semiconductors. Abstract : We critically readdress the definition of thermal boundary resistance at an interface between two semiconductors. By means of atomistic simulations we provide evidence that the widely used Kapitza formalism predicts thermal boundary resistance values in good agreement with the more rigorous Onsager non-equilibrium thermodynamics picture. The latter is, however, better suited to provide physical insight on interface thermal rectification phenomena. We identify the factors that determine the temperature profile across the interface and the source of interface thermal rectification. To this end we perform non-equilibrium molecular dynamics computational experiments on a Si–Ge system with a graded compositional interface of varying thickness, considering thermal bias of different sign.